2022
DOI: 10.3390/cancers14092058
|View full text |Cite
|
Sign up to set email alerts
|

Optical Genome Mapping as a Diagnostic Tool in Pediatric Acute Myeloid Leukemia

Abstract: Pediatric AML is characterized by numerous genetic aberrations (chromosomal translocations, deletions, insertions) impacting its classification for risk of treatment failure. Aberrations are described by classical cytogenetic procedures (karyotyping, FISH), which harbor limitations (low resolution, need for cell cultivation, cost-intensiveness, experienced staff required). Optical Genome Mapping (OGM) is an emerging chip-based DNA technique combining high resolution (~500 bp) with a relatively short turnaround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Around 20% of leukemic blasts are required for SNP-array in a diagnostic setting for large CN alterations. 34,35 Our study and others 14,36,37 showed that OGM performance on samples with blast amounts of about 20%-30% could also detect observed by conventional diagnostic methods. Hence, OGM could be an attractive option for routine diagnostic workup of hematological malignancies, as it has a fast turnaround time of ≈5 days from sample acquisition to data analysis.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Around 20% of leukemic blasts are required for SNP-array in a diagnostic setting for large CN alterations. 34,35 Our study and others 14,36,37 showed that OGM performance on samples with blast amounts of about 20%-30% could also detect observed by conventional diagnostic methods. Hence, OGM could be an attractive option for routine diagnostic workup of hematological malignancies, as it has a fast turnaround time of ≈5 days from sample acquisition to data analysis.…”
Section: Discussionsupporting
confidence: 60%
“…The applicability of this approach has recently been shown for various hematological malignancies, and some researchers even advocate for further replacing the existing routine diagnostics methods of those neoplasms with optical genome mapping (OGM). 11–17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the adult population, one patient was re-classified, leading to changes in treatment. For two patients, an MRD marker could be identified [ 32 ].…”
Section: Optical Genome Mapping In Aml—concordance With Standard Diag...mentioning
confidence: 99%
“…Nowadays, there are some cytogenetic and molecular methods used in SV detection, with different advantages and limitations. Methods used to detect genetic aberrations vary in their resolutions, which may affect the more precise assignment of the gene being tested [4]. For instance, karyotyping analysis allows for the identification of balanced and unbalanced structural anomalies, limited by the proliferation index of the blast, as well as by the poor quality of the metaphases obtained and the low resolution (about 5 Mbp) [5].…”
Section: Introductionmentioning
confidence: 99%